Development of nutrition education programme for HIV/AIDS affected orphans in peri-urban informal settlement - Senoelo, S. J. (My University, 2013)
Introduction and purpose: This empirical study was carried out to determine the nutritional status and level of nutritional knowledge amongst orphaned children. A cycle menu will be developed after sensory evaluations of all protein enhanced dishes. Method: Anthropometric measures were used to determine the nutritional status and to measure the nutrition knowledge of 100 orphaned children aged 9 to 13 years old in Boipatong, Vaal region. A nutritional knowledge questionnaire was administered to the study group. Furthermore the anthropometric measurement was carried out and analysed with World Health Organization software (AnthoPius) using ±2 standard deviations cut off points, and data on nutritional knowledge were captured on Microsoft Excel and analysed for frequencies, mean and standard deviation (SD) using the Statistical Package for Social Science (SPSS) version 1'7. Results: The results for nutritional status revealed that 59% of the population studied were underweight, 40% were stunted and 25% were wasted. Most of the respondents (70%) scored less than 50% on the nutrition knowledge questionnaire. The mean correct answer for multiple choice questions was 29.65% and for true/false question was 50.34%. Conclusion: The orphaned children are under-nourished and wasted. Further to this, the nutrition knowledge of the orphans is poor. It is recommended that a nutrition education programme be implemented so as to address the issue of poor food choices and malnutrition.
xxi, 199 leaves: ill.
Keywords: Nutrition of orphaned children; HIV/AIDS orphans; Nutrition education; 614.59690968; Malnutrition in children; AIDS (Disease); HIV infections